An analysis on the correlation structure between equity risk premium and volatility. Issue 4 (3rd July 2016) - Shi, Lelai; Kang, Canhua
Abstract: This paper explores the variation and interactions between stock volatility indicators and the market price of risk through a bivariate model. The result reveals that the daily risk premiums of the two indicators follow similar patterns and the GARCH (1, 1) indicator is the most consistent to the predication. For the selected samples, we don't find strong evidence of leverage and volatility feedback effects. However, when the impact of financial crisis on volatility is taken into account, we find apparent leverage and volatility feedback effects for both volatility indicators after re-sampling, which implies that there exist asymmetric effects in Chinese stock market.